Principles of professional development of future agronomist (Pedagogy of Higher and Secondary Education, 2012)
Kurbatova YU. V. Principles of professional development of future agronomist.The model of professional development of the future agronomist in the teaching and educational process of agrarian university and detailed principles of future agronomist professional development are considered in this article.
Keywords: professional formation; development of professional formation; pedagogical principles; pedagogical conditions